Table of Content - - (Journal of Humanities & Social Sciences, 2024)
Table of Content: 1. Difficulties Faced by Married Female Employees at the University of Zakho Dr. Sajida Ismail Abdullah 2. Pollination operations and field organization in the territory of the Taza Province – Morocco Dr. ABDELOUAHED BOUBERRIA, Dr. Abdelhafid Hammimi, Dr. Mohammed Abahrour, Dr. Mohammed Errafik 3. Lynch Company’s River Navigation Franchises in Mesopotamia: Economic Control and Local Responses 1860-1908 Ali Mohammed Qader